2021
DOI: 10.46328/ijres.1471
|View full text |Cite
|
Sign up to set email alerts
|

Mind Games with the Views of Classroom Teachers

Abstract: This study aimed to determine the views of classroom teachers about mind games in Turkey and a survey model was used. The research was carried out with the phenomenological design from qualitative research methods. Thirty-one primary school teachers were selected by the criterion sampling method which is one of the purposeful sampling methods. In order to collect the data, the opinion form prepared by the researcher was completed by classroom teachers. The documents obtained were analyzed with the content anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…However, they stated that large class sizes and management issues would be barriers to implementing intelligence games in education. These findings are in line with the literature, where views of classroom teachers also revealed similar barriers (Kula, 2021). Cole-Hamilton, Harrop, and Street (2002) also stated that especially the large class size and the lack of classroom assistants are important limitations in their systematic review study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, they stated that large class sizes and management issues would be barriers to implementing intelligence games in education. These findings are in line with the literature, where views of classroom teachers also revealed similar barriers (Kula, 2021). Cole-Hamilton, Harrop, and Street (2002) also stated that especially the large class size and the lack of classroom assistants are important limitations in their systematic review study.…”
Section: Discussionsupporting
confidence: 87%
“…Educational games can be very effective on children's physical, mental, social, emotional, and language development. Especially with the emergence of today's student-centered modern approaches, they have come to the fore even more (Kula, 2021;Sütçü, 2020;Taş & Yöndemli, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The activity games especially the 'brain factor game' were effective in promoting students' creativity and critical thinking. Kula (2021) found that mind games contribute to students' communication, creativity, problem solving, mathematical and logical thinking, and academic skills for their functioning in the world. Every student irrespective of the geographical location should have the opportunity to learn to think mathematically and reason mathematically (both deductive and inductive) in classrooms (OECD, 2021b), and teachers can provide this opportunity through mind games.…”
Section: Brain Factor Gamementioning
confidence: 99%
“…Geometrik-mekanik zekâ oyunlarının uygulandığı deney grubunda öğrencilerin üç boyutlu geometrik düşünme testi (3BGT) fark puanları cinsiyete göre farklılaşmakta mıdır? Alanyazında zekâ oyunlarının öğrencilerin akademik başarısını, iletişim, yaratıcılık, problem çözme, mantıksal-matematiksel düşünme becerilerini olumlu etkilediği (Şahin, 2019;Kula, 2021), akıl yürütme ve muhakeme etme (Reiter, Thorton ve Vannebush, 2014), dikkat ve görsel algı (Altun, 2017;Yağlı, 2019) ile zihinsel beceri düzeylerini artırdığı (Marangoz, 2018), motivasyonu ve matematik öğrenimini etkileyerek zekâ bölümlerini (IQ) (Chizary ve Farhangi, 2017) geliştirdiği görülmüştür. Bununla birlikte düzlemsel ve uzamsal modelleme kullanılarak öğretici oyunlarla yapılan öğretimin ortaokul öğrencilerinin uzamsal görselleştirme becerilerini geliştirdiği (Totikova, Yessaliyev, Madiyarov, Medetbekova, 2020), geometrik mekanik zeka oyunları uygulamalarının uzamsal düşünme becerilerini (Demirkaya ve Masal, 2017), dinamik geometri bilgisayar yazılımı kullanımının ise 9.sınıf düzeyindeki öğrencilerin geometrik düşünme becerilerini attırdığı (Adelabu, Makgato, Ramaligela, 2019) görülmüştür.…”
Section: Geometrik Mekanik Zekâ Oyunlarının İlköğretim 3 Sınıf öğRen...unclassified